Attitude of communities toward rural tourism development - Lo, May-Chiun; T., Ramayah; Helen, Lee Hui Hui (Zhengzhou University, 2013)
The rapid development of the tourism industry has detrimental impacts to the environment especially in the depletion of natural resources and the degradation of the eco-system. Hence, the potential hostile responses expected from the local communities would negatively affect any rural tourism development, if equilibrium between benefits and negative effects of the development are not properly achieved. Thus, the purpose of this study is to assess the perceptions of rural tourism communities and their aspiration towards tourism development from five main environmental perspectives, namely destination environment, communities' satisfaction, environmental management practices, influence of environmental resources, and communities' attitudes at rural destinations in Malaysia. One hundred and eighty-two respondents comprising of residents of rural tourism in Malaysia took part voluntarily in this study. Interestingly, the findings revealed that local communities' satisfactions and influence of resources at the rural destinations were of the most concerned to the local communities with regards to their future aspirations towards tourism development.